2002
DOI: 10.1016/s0012-821x(01)00562-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in remanence, coercivity and domain state at low temperature in magnetite

Abstract: Submicron magnetite crystals with mean sizes of 0.037, 0.10 and 0.22 Wm undergo major changes in hysteresis properties and domain states in crossing the Verwey transition (T V W120 K). The 0.037 Wm crystals are single-domain (SD) both in the cubic phase at room temperature T 0 and in the monoclinic phase below T V . The 0.10 and 0.22 Wm crystals have a mixture of SD and two-domain (2D) states at room temperature T 0 , but mainly SD structures below T V , in agreement with micromagnetic calculations. Coercive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 43 publications
12
116
1
Order By: Relevance
“…Coercive force is practically temperature independent above the Verwey transition (105 K) and increases by factor of 4 below this transition. The increase in H c in the vicinity of T v has been observed previously [3] for submicron magnetite nanoparticles with medium particle sizes ≤ 0.22 µm. This increase reflects the large increase in magnetocrystalline anisotropy in the cubicmonoclinic phase transition.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Coercive force is practically temperature independent above the Verwey transition (105 K) and increases by factor of 4 below this transition. The increase in H c in the vicinity of T v has been observed previously [3] for submicron magnetite nanoparticles with medium particle sizes ≤ 0.22 µm. This increase reflects the large increase in magnetocrystalline anisotropy in the cubicmonoclinic phase transition.…”
Section: Resultssupporting
confidence: 78%
“…The results from measurements of remanence and coercive force measured in the monoclinic phase (below T v ) for fine grained magnetites with medium particle sizes of 0.037, 0.10 and 0.22 µm have showed that coercive force H c and remanence magnetization increase on cooling through T v in submicron magnetite particles [3]. These increases reflect the large increase in magnetocrystalline anisotropy and magnetostriction in the cubic → monoclinic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…4a; Muxworthy and McClelland 2000;Özdemir et al 2002). During warming of the RT-SIRM, the remanence is not fully recovered when passing the temperature of the Verwey transition.…”
Section: Low-temperature Measurementsmentioning
confidence: 99%
“…These measurements allow the recognition of the magnetic minerals based on their characteristic magnetic behavior below room temperature. The most common observation in the studied samples is the drop of the remanence acquired at room temperature (RT-SIRM) at 110-120 K, which corresponds to the Verwey transition of magnetite [47,48]. This feature is observed throughout the entire studied transect from SW to NE.…”
Section: General Trendsmentioning
confidence: 88%